Atomistic properties of solids - Sirdeshmukh, D. B. (Dinker B.) 1935-; Sirdeshmukh, L. (Lalitha) 1935-.; Subhadra, K. G. 1947-.; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
The book deals with atomistic properties of solids which are determined by the crystal structure, interatomic forces and atomic displacements influenced by the effects of temperature, stress and electric fields. The book gives equal importance to experimental details and theory. There are full chapters dedicated to the tensor nature of physical properties, mechanical properties, lattice vibrations, crystal structure determination and ferroelectricity. The other crystalline states like nano-, poly-, liquid- and quasi crystals are discussed. Several new topics like nonlinear optics and the Rietveld method are presented in the book. The book lays emphasis on the role of symmetry in crystal properties. Comprehensiveness is the strength of the book; this allows users at different levels a choice of chapters according to their requirements.
Introduction -- Crystal growth -- Crystallography -- Diffraction of radiation by crystals -- Crystal structure determination -- Cohesion -- Tensor nature of crystal properties -- Mechanical properties -- Thermal properties -- Lattice vibrations -- Dielectric properties -- Pyro-, Piezo- and ferroelectricity -- Optical properties of insulators -- Defects in crystals: I Point defects -- Defects in crystals: II Dislocations -- The other crystalline states (quasi crystals, nano crystals, polycrystals, thin films, liquid crystals).
Electronic reproduction.
Keywords: Physics; Solids; Electronic books